DOA Estimation Based on Average Processing of Redundant Virtual Array Elements for Coprime MIMO Radar. Issue 1 (April 2021) - Zhang, Yule; Hu, Guoping; Zhu, Mingming; Zhan, Chenghong; Zhao, Feilong; Zhou, Hao; Zhao, Fangzheng; Yue, Shijie
Abstract: The redundant virtual array elements formed by the sum and difference coarray (SDCA) are always discarded in the existing DOA estimation methods, which could cause effective information loss and poor performance. In this paper, a new technology based on average processing of redundant virtual array elements is proposed for coprime MIMO radar direction of arrival (DOA) estimation. Then, Toeplitz matrix reconstruction based on MUSIC algorithm is employed to validate the effectiveness of the proposed technology for DOA estimation.